Expected Hepatocarcinoma Cancer Rate Due to Escape Mutant among Local Population in Thailand: The Situation after the Implementation of Universal Hepatitis B Vaccination at Birth - Joob, Beuy; Wiwanitkit, Viroj (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Chronic hepatitis B infection is an etiology of hepatocellular carcinoma. The high prevalence of hepatitis B can be seen in several regions including Indochina. In Thailand, a country in Indochina, according to the local public health policies, the universal hepatitis B vaccination is freely given to any infant at birth without charge. Despite the universal vaccination, the hepatitis B seropositive rate is still observed, and it can still be a cause of hepatocellular carcinoma among the hepatitis B carriers in the future. Methods: Here, the authors try to estimate the expected hepatocarcinoma cancer rate due to escape mutant among local population in Thailand, the situation after the implementation of universal hepatitis B vaccination at birth. Results: Based on the present study, the mutant escape contributes to only a few parts of overall estimated cancer cases in the situation that there is an implementation of universal hepatitis B vaccination at birth. Conclusion: Efficacy of theuniversal hepatitis B vaccination is not improved by specific management on escape mutants.
Keywords: Escape mutant; hepatitis B; Thailand; universal; vaccination